Análise e interação de duas variáveis do treinamento físico na prática cotidiana : alongamento e força - Netto, Sebastião Barbosa (2015)
Flexibility and muscle strength are two variables of physical training rather investigated in the scientific literature. Differences in studies results are found when stretching exercises preceding strength, regardless of the type of stretching or strength investigated. In the current decade, there is a concern to bring together the studies conducted in laboratory environment and professional practice, the socalled ecological validity, in intention to provide results applicable in daily life. Thus, the thesis objectives were: a) identify which intensity strength training practitioners usually to train in their workout routines; b) identify as the prescription of stretching exercises in the gym and strength training centers is carried out; c) evaluate the effect of stretching exercises (split vs. continuous) on muscle strength; d) identify the duration of the deleterious effect of stretching exercises on muscle strength. Briefly, there was an analysis of stretching and muscle strength in everyday practice. Regarding the strength, we identified that the strength training practitioners do not reach maximum levels of intensity in your workout routines. With regard to stretching exercises, the prescription is performed in intention to prevent muscle soreness and injury and the most used method is static stretching. When there was the interaction of these two variables, one stretching exercise caused no loss in strength production, whether carried out continuously or discontinuously. However, by increasing the number of exercises and the total time of stretching the immediate ability to generate muscle strength decreased, being restored after 5 minutes.